Allocation strategies for nitrogen and phosphorus in forest plants. Issue 10 (23rd May 2018) - Zhang, Jiahui; He, Nianpeng; Liu, Congcong; Xu, Li; Yu, Qiang; Yu, Guirui
Abstract : The allocation of limiting elements, such as nitrogen (N) and phosphorus (P), in plants is an important basis for structural stability and functional optimization in natural plant communities. However, because of the lack of systematic investigation data, the mechanisms of optimal nutrient allocation in plants in natural forests are still unclear. Using consistent measurements of N and P contents in 930 plant species, we explored the allocation strategies for N and P in different plant organs and plant functional groups (PFGs) in natural communities. The N and P contents and N:P ratio were the highest in the leaf (the most active organ) at the organ level. At the PFG level, the N and P contents were higher in herbs than in woody plants, but the trend was opposite for the N:P ratio. The elemental plasticity of root was higher than that of leaf. Furthermore, at the large scale, the allometric exponents of N and P were less than 1 and showed no difference, indicating strong conservatism of the scaling relationship in plants. In summary, higher element content in more active organs, higher element plasticity in underground organs, and conservative allometric allocation among different organs and among different PFGs jointly constitute the optimal strategies for the allocation of limiting elements.